DIGITALIZATION OF AGRICULTURE AND FOOD SECURITY IN SOUTH SULAWESI: CHALLENGES, POLICY RESPONSES, AND PATHWAYS TOWARD SUSTAINABLE SELF-SUFFICIENCY - Zulkifli Sjamsir; Besse Dahliana; Suhartina R (PT. Jurnal Center Indonesia Publisher, 2026)
This study examines the digitalization of agriculture and its implications for food security in South Sulawesi, focusing on structural challenges, policy responses, and pathways toward sustainable self-sufficiency. Despite relatively stable rice production, food security in the province remains vulnerable to climate variability, irrigation constraints, fragmented distribution systems, and uneven digital integration. Using a mixed-method approach that combines quantitative survey data and qualitative policy analysis, this research evaluates the relationship between digital adoption and farmer performance. The findings indicate that farmers utilizing digital tools demonstrate higher production stability, stronger market price awareness, and better planting planning accuracy compared to non-digital farmers. However, digital literacy gaps and limited institutional coordination constrain broader system transformation. Policy responses remain largely reactive and sectorally fragmented. The study proposes a Digital-Sustainable Self-Sufficiency Framework that integrates digital infrastructure expansion, smart irrigation governance, supply chain monitoring, and inter-agency coordination. The findings suggest that digitalization should be positioned not merely as technological adoption but as a governance transformation mechanism to strengthen adaptive capacity, enhance coordination, and achieve resilient and sustainable food security.